PEMAHAMAN LITERASI KEUANGAN DALAM PENGGUNAAN PINJAMAN ONLINE PADA E-COMMERCE SHOPEE PAYLATER - Nursinta, Lia Ayu; Subagyo; Widodo, Moch. Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to find out how to understand financial literacy in the use of online loans in shopee paylater e-commerce. This research uses a qualitative approach with the type of ethnomethodological research. The way this research data is collected is through observation, interviews, and documentation. The criteria for determining informants in this study include relevance, recommendation, rapport, readiness, reassurance (5R). The informant in this study was a management study program student class of 2018 who used shopee payleter. The findings of this study show that the aspects of financial literacy in savings, loans and financial management show their measurements in well literate while in investment and insurance show measurements in sufficient literacy, which means that students' understanding of financial literacy is quite good.